The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1037/1541-1559.5.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Who requests psychological services upon admission to prison?

Abstract: Federal Bureau of PrisonsStructuring a system of psychological services for offenders and releasees requires an understanding of the offenders who voluntarily seek psychological services upon admission. To begin to develop such an understanding, a sample set of responses to the Psychological Services Inmate Questionnaire (PSIQ) from 2,674 newly committed male and female federal offenders were examined. About one-tenth of the sample made a request for psychological services upon admission to prison without a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
4
23
1
Order By: Relevance
“…This finding reflects a similar pattern in the community [12]. Only two studies focused on women only [44,60] and three studies generated gender-specific prevalence rates [22,40,58]. Study samples, overall, were predominantly male and from white ethnic backgrounds.…”
Section: Theme 1: the Varied Prevalence Of Insomniasupporting
confidence: 63%
See 2 more Smart Citations
“…This finding reflects a similar pattern in the community [12]. Only two studies focused on women only [44,60] and three studies generated gender-specific prevalence rates [22,40,58]. Study samples, overall, were predominantly male and from white ethnic backgrounds.…”
Section: Theme 1: the Varied Prevalence Of Insomniasupporting
confidence: 63%
“…With regards to criminogenic factors, three studies examined unconvicted and sentenced prisoners, finding that insomnia tended to be more common in the former [22, 43,44]. Overall, insomnia symptoms prevalence was higher in a prison population than in the general population (30%e 36%) [8] with the exception of just two studies (10.9% and around 20%) [40,51]. The former study identified this figure based on whether the prisoner had been prescribed hypnotic medication only and not by prisoner self-report of insomnia symptoms.…”
Section: Theme 1: the Varied Prevalence Of Insomniamentioning
confidence: 94%
See 1 more Smart Citation
“…The PSIQ also includes two checklists, one regarding drug use for the two years preceding arrest and one regarding the experience of any recent psychological symptoms. The PSIQ is completed prior to a clinical interview with a BOP doctoral-level psychologist which allows the psychologist to review the inmate's selfreported prior history, along with other criminal and mental health records, in advance of the clinical interview (Diamond, Magaletta, Harzke, & Baxter, 2008).…”
Section: The Psychology Services Inmate Questionnaire (Psiq)mentioning
confidence: 99%
“…The Office of Research and Evaluation of the BOP provided SENTRY data after they were provided with identification numbers for all inmates participating in the study. Four independent coders were trained to code data from PSIs onto the PSI-Coding Form (PSI-CF), and they were trained to achieve at least 80% reliability before they began coding data (Diamond et al, 2008;Magaletta et al, 2009).…”
Section: Psychological Assessment Inventory (Pai)mentioning
confidence: 99%